Multimodal Perineural Analgesia with Combined Bupivacaine‐Clonidine‐Buprenorphine‐Dexamethasone: Safe In Vivo and Chemically Compatible in Solution. Issue 1 (23rd October 2014) - Williams, Brian A.; Butt, Mark T.; Zeller, Jillynne R.; Coffee, Samantha; Pippi, Michael A.
Abstract Objectives The use of adjuvants in regional anesthesia has increased. However, there are knowledge gaps pertaining to 1) in vivo local tissue effects of these adjuvants; and 2) chemical compatibility and solubility of these drugs in solution with each other and with local anesthetics. This study addresses these gaps in knowledge. Design In vivo rat safety/toxicopathology study and analytical chemistry study. Setting Collaborating Good Laboratory Practice laboratories under the direction of the university‐based principal investigator. Methods Single‐injection formulations of clonidine, buprenorphine, and dexamethasone were combined with either bupivacaine or midazolam, and were administered to groups of rats. Post‐injection behavior was monitored to assess changes related to the block. A continuous infusion of bupivacaine, clonidine, and dexamethasone was administered to another group of rats, and behavioral effects were recorded. After 15 days, rats were sacrificed and their nerves/dorsal root ganglia were examined by the pathologist. Samples of combined drug solutions were processed at an analytical chemistry laboratory for compatibility, solubility, and stability. Results Each of the single‐injection formulations produced reversible sensory and/or motor block. None of the study drugs caused damage to any of the nerve segments or related tissue. The text describes the concentrations at which compatibility and solubility of the combined drug solutions were achieved. Conclusions Four‐drug single‐injection formulations are described that 1) had compatible and stable concentrations in solution; and 2) produced reversible nerve block without causing long‐term motor or sensory deficits or damage to sciatic nerves/dorsal root ganglia.